Monitoring of a Double Skin Façade Building: Methodology and Office Thermal and Energy Performance - Marques da Silva, F. (2013)
This paper concerns to the post-occupancy monitoring of a building sited in Lisbon with transparent double-skin façades. This is the first of an enlarged monitoring program covering other buildings and weather conditions, aiming to clarify under which climate and performing conditions this architectural solution is acceptable. Within this campaign an enlarged set of parameters was measured from external conditions to energy consumption and indoor comfort. The present paper describes the building, presents the monitoring methodology and analyses the thermal and energy performance of a specific office space.